1999
DOI: 10.1046/j.1365-2443.1999.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Nps1/Sth1p, a component of an essential chromatin‐remodeling complex of Saccharomyces cerevisiae, is required for the maximal expression of early meiotic genes

Abstract: Background: The NPS1/STH1 gene of Saccharomyces cerevisiae is essential for mitotic growth, especially for the progression through the G2/M phase. It encodes a major component of the chromatinremodelling complex, RSC, of unknown function. We attempted to address the function of NPS1 in meiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 75 publications
0
24
0
1
Order By: Relevance
“…Other observations do however connect the RSC complex with transcription. Some rsc mutations a ect the expression of the CHA1 gene as well as certain genes involved in early meiosis (Moreira and Holmberg, 1999;Yukawa et al, 1999). The RSC complex also appears to cooperate with histone acetylases.…”
Section: Swi/snf Complexes In Saccharomyces Cerevisiaementioning
confidence: 99%
“…Other observations do however connect the RSC complex with transcription. Some rsc mutations a ect the expression of the CHA1 gene as well as certain genes involved in early meiosis (Moreira and Holmberg, 1999;Yukawa et al, 1999). The RSC complex also appears to cooperate with histone acetylases.…”
Section: Swi/snf Complexes In Saccharomyces Cerevisiaementioning
confidence: 99%
“…3) We observed previously that nps1-105, rsc1Á or rsc2Á mutation shows a notable decrease and delay in the expression of IME2 with a slight decrease in IME1 expression. 10,11) Northern blot analysis of the expression of these two early-meiotic genes in WT (W303D), nps1-105 (WTH1D) and nps1-13 (WHK13-D) strains carrying each plasmid were grown to early log phase in a minimal selection medium followed by cultivation in YPAc to early stationary phase. The cells were then shifted to sporulation medium and samples were removed at the indicated times to monitor sporulation.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that the homozygous diploid of the temperature sensitive nps1-105 mutant or the deletion allele of either the RSC1 or the RSC2 genes showed reduced expression of several early-meiotic genes, and sporulates poorly. 10,11) The nps1-105 mutation harbors an amino acid substitution within the ATPase domain, and the RSC1 and the RSC2 genes encode additional components of RSC.…”
Section: Rsc Nucleosome-remodeling Complex Plays Prominent Roles In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Previous studies have indicated that acceleration of histone H3 acetylation at URS1 by Gcn5/HAT is essential for the activation of IME2, in addition to Ime1 and the ATP-dependent chromatin-remodeling complex RSC. 11,12) The molecular mechanisms underlying the transition from hypoacetylated repressive chromatin state maintained by the Rpd3-Sin3/HDAC complex to hyperacetylated active chromatin by Gcn5 at the URS1 of IME2 have been of much interest, because URS1 was bound by Ume6 under all conditions tested. It has long been thought that the binding of Ime1 to Ume6 excludes or inhibits the HDAC complex to allow H3 acetylation by Gcn5.…”
mentioning
confidence: 99%